Understanding Relations Between Scripts II Early Alphabets - Boyes, Philip J.; Steele, Philippa (Oxbow Books, 2020)
The conference Understanding Relations Between Scripts II: Early Alphabets took place in March 2017 at the Faculty of Classics, Cambridge. This was the first of a programme of collaborative events organised as part of the project Contexts of and Relations between Early Writing Systems (CREWS), which pursues interdisciplinary research into the development and context of writing around the Mediterranean and Levant in the second and first millennia BC. CREWS has received funding from the European Research Council (ERC) under the European Union's Horizon 2020 research and innovation programme (grant agreement No 677758).